A new non-Andean South American Chysis (Bletiinae-Orchidaceae) with pale flowers - Petini-Benelli, Adarilda; Pessoa, Edlley (Phytotaxa, 2019)
A new species of Chysis sect. Chysis is described from the Central-West region of Brazil. It is similar to C. aurea and C. bruennowiana, the other two South American species of the genus, but differs in the pale pink perianth with magenta stripes or dots on the labellum and on the abaxial surface of the column, and by a labellum that is wider than long with the mid-lobe not surpassing the length of the lateral lobes. The species, which confirms the presence of the genus in the Brazilian plateau, had been previously misidentified as C. laevis. Photographs, an illustration, and a key to the South American species are provided.